Chemogenic Synthesis of Chromium Oxide Nanoparticles using Sol-Gel Method and its Potential on Pancreatic Lipase Inhibition - Cheah, Shi Yan; Tey, Lai-Hock; Mohammod, Aminuzzaman; Akira, Watanabe (INTI International University, 2022)
Obesity is a chronic disease which has been linked with several metabolic disorders. Till now, there is no ideal pharmacological treatment has been developed for obesity treatment. A nanoparticle or ultrafine particle has attracted the attention of researchers due to its unique physiochemical characteristics as a subject tool for physics, chemistry, and biology studies. One of the promising trace elements, chromium, has played a crucial role in the regulation of blood sugar levels and carbohydrates and fats degradation metabolism. Within our project, chromium has been synthesized into chromium oxide nanoparticles (Cr2O3 NPs) using sol-gel method, which has a higher surface area and an oxidizing potential. Chemogenic synthesized Cr2O3 NPs were characterized using UV-Vis Spectrophotometer (UV-Vis), Fourier Transform Infrared Spectroscopy (Ft-IR), Scanning Electron Microscope (SEM), and Energy Dispersive X-Ray Spectroscopy (EDX) confirm the formation and morphology of nanoparticles. Cr2O3 NPs were in spherical shape with an average size of 67.9 nm under SEM analysis and chromium (Cr) (56.7%) and oxygen (O) (43.53%) were analyzed using EDX. Two peaks (272 nm, 368 nm) were shown in UV-Vis characterization and two sharp peaks, 574 cm-1 and 640 cm-1 were present in Ft-IR analysis. Lastly, the pancreatic lipase inhibitory assay, which reduces the absorption of fats into the gastrointestinal system, was appraised on Cr2O3 NPs with 89.48% of inhibition, with half-maximal inhibitory concentration (IC50) at 31.70 ± 2.14 (µg/mL) ± SE.